Kontribusi Social Support terhadap Hardiness pada Mahasiswa Fakultas Psikologi - Kristofer Biaggi Susanto; Heliany Kiswantomo (Humanitas (Jurnal Psikologi), 2020)
This study aims to examine the contribution of social support to hardiness in college students. This study uses social support (a= 0.86) and hardiness questionnaire (a= 0.82), which compiled by the authors. Through a purposive sampling technique, 204 college students were collected, and after analysis using a binary logistic regression test, it was found that four types of social support contributed significantly to hardiness. The biggest contribution was provided from tangible support (R2 = 20.9%), and the smallest contribution was from belonging support (R2 = 8.8%). In summary, all of the social support was needed by a college student to increase hardiness, and tangible support is most needed. For further research, it is advisable to examine the simultaneous contribution of combination in several social support types to hardiness. Keywords: Hardiness, Social Support, Contribution